Methods for quantification and analysis of microplastics present in aqueous matrices

The process of using magnetic iron material particles and a microwave-enhanced Fenton process effectively addresses the challenge of quantifying microplastics in aqueous matrices by efficiently separating and oxidizing non-plastic organic particles, achieving high yields and operational efficiency.

JP2025507274APending Publication Date: 2025-03-18CAPTOPLASTIC SL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024545230
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-27
Filing Date
2023-01-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Current methods for quantifying microplastics in aqueous matrices are inefficient due to interference from non-plastic organic particles, requiring aggressive treatments that can damage microplastics or result in incomplete separation.

Method used

A process involving the use of magnetic iron material particles to form aggregates with microplastics and non-plastic organic particles, followed by magnetic separation and a microwave-enhanced Fenton process for selective oxidation of organic particles, allowing for efficient quantification of microplastics without damaging them.

Benefits of technology

This method achieves high yields (>80% for organic particle removal and >95% for microplastic quantification) with reduced time and reagent consumption, using environmentally friendly reagents and simple equipment, while maintaining the integrity of microplastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507274000042
    Figure 2025507274000042
  • Figure 2025507274000001
    Figure 2025507274000001
  • Figure 2025507274000002
    Figure 2025507274000002
Patent Text Reader

Abstract

The present invention relates to a process for the quantification and analysis of microplastics contained in an aqueous matrix, comprising magnetic separation of microplastics by interaction of said microplastics with magnetic ferrous material particles, formation of microplastic / magnetic ferrous material agglomerates, selective oxidation of non-plastic organic particles, and quantification of the separated microplastics.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention further relates to a process for determining parameters for the quantification of microplastics contained in an aqueous matrix containing other non-plastic particles, which essentially consists of magnetic separation of microplastics from the aqueous matrix after their interaction with magnetic ferrous material particles and the formation of microplastic / magnetic ferrous material agglomerates, selective oxidation of organic (non-plastic) solid particles that can be separated together with the microplastics in a first step. The invention also relates to a process for the quantification of microplastics in said aqueous matrix using the predetermined parameters. [Background technology]

[0002] Due to the excellent properties of plastics, among which the ease of molding, high mechanical and chemical resistance, and low cost stand out, plastics are widely used both in industry and society as a whole. Since the development of the first synthetic polymers in the mid-20th century, the production of these synthetic polymers has not stopped growing. In 2019, the global production of plastics reached 370 million tons (PlasticsEurope, 2020), and the production of plastics is expected to double in the next 20 years (MacArthur, DE et al., The New Plastics Economy: Rethinking the Future of Plastics. World Economic Forum. (2016)). Although plastics are certainly useful, the generation of plastic waste and its improper management are significant environmental issues.

[0003] Removal of plastics is not a problem when the plastics are large in size. However, with use, plastics decompose, generating smaller pieces of plastic that are more difficult to remove (especially when the pieces have a diameter of millimeters). Microplastics are defined as plastic particles with a size of less than 5 mm (Bergmann, M. et al., Marine Anthropogenic Litter (2015) Springer) and are traces of plastics that are widely present in the environment. Microplastics have been found in virtually all ecosystems on Earth, including inland and marine waters, sediments, air, and soil (Grbic, J. et al., Environmental Science and Technology Letters 6 (2019) 68-72). They are therefore present in living organisms (Cole, M. et al., Nature Scientific Reports 4: 4528 (2014) 1-8; Wieczorek, A. M. et al., Environmental Science and Technology 53 (2019) 5387-5396), essentially aquatic organisms, so there is considerable concern about the potential damage their presence could have both in humans and in fauna (Wright, S. Let al., Environmental Science and Technology 51 (2017) 6634-6647; Cox, K. D. et al., Environmental Science and Technology 53 (2019) 7068-7074).

[0004] It is estimated that 80% of the microplastics present in the ocean originate directly from rivers (Li, J. et al. Water Research 137 (2018) 362-374). And rivers are the main recipients of effluents from urban and industrial wastewater treatment plants (WWTPs), which have been identified as an important source of introducing microplastics into the aquatic environment (Li, J. et al. Water Research 137 (2018) 362-374). In this aspect, the development of equipment that allows the treatment of microplastic-contaminated water is clearly a relevant challenge.

[0005] On the other hand, in order to assess the true impact of microplastics and their distribution in the environment, as well as to formulate specific regulations in this field, it is essential to carry out a proper quantification and characterization of these particles in the different aqueous matrices that may contain them (WWTP effluents, drinking water, rivers, lakes, reservoirs, and oceans, among others). The analysis of these particles is particularly complex given their very heterogeneous size, shape, color, density, and chemical composition. In a recent literature review (Koelmans, AA et al. Water Research 155 (2019) 410-422), 50 papers that studied the presence of microplastics in inland waters and drinking water were analyzed. It was concluded that many of the papers could not be considered completely reliable. The biggest challenge is the very small microplastics, i.e. those with a size of less than 300 μm. For example, sampling with a net with a pore size of 80 μm instead of 330 μm resulted in measurements of concentrations 250 times higher (Dris, R. et al. Environmental Chemistry 12 (2015) 592-599). Given the series of published studies on the presence of microplastics in inland waters, there is a clear need to develop effective sampling systems for the analysis of microplastics. Indeed, a recent World Health Organization report entitled "Microplastics in drinking-water" (World Health Organization (2019) ISBN 978-92-4-151619-8) highlighted the development of methods for sampling and analysis of microplastics as a necessary priority in research.

[0006] The analysis of microplastics present in the aqueous matrix to be evaluated requires several steps (Prata, JC et al. Trends in Analytical Chemistry 110 (2019) 150-159). First, the microplastics must be extracted from the aqueous matrix. Secondly, the solid particles separated in the first step must be treated with the aim of eliminating possible interferences, basically organic particles. Thirdly, a step of separating microplastics may only be required if the sample has a high content of non-plastic solids. Finally, the microplastics are quantified and characterized.

[0007] Filtration or sieving is the most common method for separating microplastics from aqueous matrices (Prata, JC et al. Trends in Analytical Chemistry 110 (2019) 150-159). The pore size of the filters or sieves used varies widely and logically determines the size of microplastics that can be separated. Nevertheless, very small pore sizes are usually avoided because they cause clogging problems due to the presence of other solids in suspension in the water, and moreover, using very small pore sizes consumes a lot of time. Therefore, small pore sizes (0.45-100 μm) are usually only used in the analysis of particularly clean aqueous matrices such as groundwater and drinking water (Koelmans, AA et al. Water Research 155 (2019) 410-422). In that sense, Neston nets with a pore size of 333 μm and plankton nets with a pore size of 100 μm are the most commonly used directly for sampling (Stock, F. et al. Trends in Analytical Chemistry 113 (2019) 84-92; Prata, JC et al. Trends in Analytical Chemistry 110 (2019) 150-159).

[0008] There are less common methods to separate and further directly quantify microplastics from aqueous matrices, such as, for example, electrostatic separators (Felising, S. et al. Environmental Pollution 234 (2018) 20-28) and flow cytometry (Sgier, L. et al. Nature Communication 7 (2016) 11587). Nevertheless, they require specialized equipment and long analysis times, in addition to being associated with high costs. Magnetic separation of microplastics by interaction with magnetic materials is a novel process that allows to separate microplastics from water regardless of their size and nature, which represents an important advantage with respect to conventional filtration methods (Grbic, J. et al., Environmental Science and Technology Letters, 6 (2019) 68-72; Munoz, M. et al., ES 2 796 998 A1 and WO 2020 / 240069 A1). Nevertheless, its use would have entailed an increase in the density of microplastics, which would have hindered their subsequent density separation from the remaining solids present in the water, and would have also interacted with magnetic materials, such as non-plastic organic particles, which may be the reason why magnetic separation of microplastics from water for quantification has not been investigated so far.

[0009] Aqueous matrices often contain solid particles in suspension, essentially organic. These particles can interfere with the analysis of microplastics and cause an overestimation of their concentration, regardless of the extraction process used. It is therefore fundamental to use a treatment that allows to significantly reduce the interference of non-plastic organic solid particles. This is a crucial step for the analysis of these plastic particles. The most common methods for removing non-plastic solid particles in suspension are the application of acid, alkaline or enzymatic degradation or oxidation processes. For acid degradation, nitric acid showed the best results (Claessens, M. et al. Marine Pollution Bulletin 70 (2013) 227-233). Nevertheless, this is a rather aggressive method, often resulting in partial dissolution of microplastics (e.g. polystyrene and polyethylene are very sensitive to acid treatment) and / or caking of said microplastics (Stock, F. et al. Trends in Analytical Chemistry 113 (2019) 84-92). Therefore, acid digestion has not been widely used for the analysis of microplastics in aqueous matrices. Alkaline digestion has greater potential than acid digestion, since it is less aggressive for microplastics. Treatment with KOH (10% v / v) or NaOH (10M) for 24 hours at 60 °C was the most effective (Hurley, RR et al. Environmental Science and Technology 52 (2018) 7409-7417). Nevertheless, some plastics such as polycarbonate, polystyrene, or polyethylene terephthalate also degrade during treatment, with mass loss. Enzymatic digestion then appears as an interesting alternative, since it is less aggressive and less likely to damage microplastics (Prata, JC et al. Trends in Analytical Chemistry 110 (2019) 150-159). However, the enzymatic digestion effectiveness depends on the type of organic matter present in the sample.Therefore, the use of this decomposition involves several steps, often combined with a mild oxidation step using H2O2, and requires long processing times of up to two weeks (Loder, MGet al. Environ. Sci. Technol. 51 (2017) 14283-14292). Moreover, it is costly.

[0010] In this context, the use of oxidation processes represents a promising alternative for the removal of organic particles. The Fenton process stands out in particular, taking into account the simplicity of the equipment required, the speed of operation, and the low operating costs required. This process is based on the catalytic decomposition of H2O2 in the presence of iron salts in an acidic medium. This leads to the generation of the hydroxyl radical (HO·), a species with high oxidizing power and low selectivity that is able to remove a wide range of organic compounds. Several recent studies have demonstrated the viability of this system in removing non-plastic organic solid particles in suspension and facilitating the isolation of microplastics present in aqueous matrices of different nature (Tagg, A. et al. Chem. Commun. 53 (2017) 372-375; Munno, K. et al. Environ. Toxicol. Chem. 37 (2018) 91-98; Hurley, R. R. et al. Environ. Sci. Technol. 52 (2018) 7409-7417; Cunsolo, S. et al. Anal. Bioanal. Chem. 413 (2021) 3789-3799). All studies are characterized by the use of high doses of H2O2 (hundreds of g / L) and iron (1-30 g / L). The operating temperatures tested ranged from room temperature up to 60 °C, because higher temperatures caused damage and mass loss of microplastics (Munno, K. et al. Environ. Toxicol. Chem. 37 (2018) 91-98). Long reaction times, typically 24 h, were therefore required to achieve a high degree of removal of interfering organic particles. Another important limitation concerns the use of high iron concentrations (on the order of g / L), which always deposit iron precipitates on the surface of microplastics. This clearly hampers subsequent quantification.

[0011] Considering this background, the development of an analytical protocol that allows the efficient, rapid and cost-effective quantification of microplastics in aqueous matrices that additionally contain non-plastic organic particles, regardless of their composition and size, and that is applicable to aqueous matrices of different nature, would represent an important finding in this field, where there are currently no standard methods. Summary of the Invention

[0012] The inventors have surprisingly discovered that the use of microwave-enhanced Fenton process has proven to be very effective and rapid in oxidizing organic particles without affecting the substance of the microplastic particles, making this process very useful for the process of quantification of microplastics.

[0013] As shown in the examples, the yields in both the process of removing organic particles and the process of quantifying microplastics are very high (greater than 80 and 95%, respectively), regardless of the nature or size of the microplastics and despite the characteristics of the aqueous matrix. The process for quantifying microplastics of the present invention is particularly advantageous with respect to other methods included in the state of the art, since it involves a significant reduction in the time and reagent consumption necessary to achieve the quantification of microplastics in an aqueous matrix. Likewise, all the reagents used are environmentally friendly. A further advantage of the process of the present invention is the simplicity of the equipment required and the low cost of the materials and reagents used. Finally, the method shows a high reproducibility of the results obtained, which is a fundamental requirement for standardization.

[0014] Thus, a first aspect of the present invention relates to a process for determining parameters for the quantification of microplastics in an aqueous matrix comprising microplastics and non-plastic organic particles, and optionally inorganic particles, comprising: a1) providing a first sample of an aqueous matrix comprising microplastics, non-plastic organic particles, and optionally inorganic particles; b1) adding magnetic iron particles to the aqueous matrix provided in step a1) to form microplastic / magnetic iron particle agglomerates and to form non-plastic organic particle / magnetic iron particle agglomerates; c1) separating the formed agglomerates and free magnetic material particles from the mixture of step b1) by applying a magnetic field; d1) subjecting the agglomerates and free magnetic iron material particles separated in step c1) to a drying step; e1) determining the weight of the dry solid of step d1) to obtain weight A (which may also be called parameter A); f1) preparing an aqueous suspension of the agglomerates obtained in step d1) and of free magnetic iron material particles; g1) subjecting the aqueous suspension prepared in step f1) to a microwave assisted Fenton process; h1) separating, preferably by filtration, the agglomerates and free magnetic material particles present in the aqueous suspension obtained from step g1), i1) subjecting the agglomerates and free magnetic iron material particles separated in step h1) to a drying step; j1) determining the weight of the dry solid in step i1) to obtain the weight AF (which may also be called parameter AF); k1) subjecting the agglomerates and free magnetic material particles separated in step i1) to a combustion step; and l1) determining the weight of the solid obtained after step k1) and obtaining the weight AFM (which may also be called parameter AFM); Includes.

[0015] In a second aspect, the present invention relates to a process for determining parameters for the quantification of microplastics in an aqueous matrix comprising microplastics and non-plastic organic particles, and optionally inorganic particles, comprising: a2) providing a first sample of an aqueous matrix comprising microplastics, non-plastic organic particles, and optionally inorganic particles; b2) separating solids from the sample of step a2), preferably by filtration; c2) subjecting the solid separated in step b2) to a drying step; d2) Determine the weight of the dry solid of step c2) and measure the weight ST M (Parameter ST M (which may also be called e2) subjecting the dried solid of step d2) to a combustion step; and f2) Determine the weight of the solid obtained after step d2) and calculate the weight SI M (Parameter SI M (which may also be called g2) providing a second sample of an aqueous matrix comprising microplastics, non-plastic organic particles, and optionally inorganic particles; h2) adding magnetic iron particles to the aqueous matrix provided in step g2) to form microplastic / magnetic iron particle agglomerates and to form non-plastic organic particle / magnetic iron particle agglomerates; i2) separating the formed agglomerates and free magnetic material particles from the mixture of step h2) by applying a magnetic field; j2) preparing an aqueous suspension of the agglomerates separated in step i2) and free magnetic iron material particles; k2) subjecting the aqueous suspension prepared in step j2) to a microwave-assisted Fenton process; l2) separating, preferably by filtration, the agglomerates and free magnetic material particles present in the aqueous suspension obtained from step k2), m2) subjecting the agglomerates and free magnetic iron material particles separated in step l2) to a drying step; n2) Determine the weight of the dry solid in step m2) and calculate the weight STNOX A (Parameter STNOX A (which may also be called o2) subjecting the agglomerates and free magnetic material particles separated in step m2) to a combustion step; p2) Determine the weight of the solid obtained after step o2) and calculate the weight SI A (Parameter SI A (which may also be called q2) filtering the remaining aqueous fraction obtained after the separation of step i2); r2) subjecting the solid separated in step q2) to a drying step; s2) Determine the weight of the dry solid of step r2) and calculate the weight ST SN (Parameter ST SN (which may also be called the t2) subjecting the dried solid of step r2) to a combustion step; u2) Determine the weight of the solid obtained after step t2) and calculate the weight SI SN (Parameter SI SN (which may also be called Includes. In a third aspect, the present invention relates to a process for the quantification of microplastics in an aqueous matrix comprising microplastics and non-plastic organic particles, and optionally inorganic particles, the process comprising: I-1) carrying out steps a1) to l1) of the process for determining parameters according to the first embodiment for determining the weights A, AF and AFM (which may also be referred to as parameters A, AF and AFM); II-1) Weight of microplastics (MP A ) to calculate:

[0016]

number

[0017]

number

[0018]

number

[0019]

number

[0020]

number

[0021]

number

[0022]

number

[0023] [Figure 1] Particle size distribution of magnetic iron mineral (magnetite) used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Process for determining parameters for the quantification of microplastics In a first aspect, the present invention relates to a process for determining parameters for the quantification of microplastics in an aqueous matrix comprising microplastics and non-plastic organic particles, and optionally inorganic particles, comprising: a1) providing a first sample of an aqueous matrix comprising microplastics, non-plastic organic particles, and optionally inorganic particles; b1) adding magnetic iron particles to the aqueous matrix provided in step a1) to form microplastic / magnetic iron particle agglomerates and to form non-plastic organic particle / magnetic iron particle agglomerates; c1) separating the formed agglomerates and free magnetic material particles from the mixture of step b1) by applying a magnetic field; d1) subjecting the agglomerates and free magnetic iron material particles separated in step c1) to a drying step; e1) determining the weight of the dry solid of step d1) to obtain weight A (which may also be called parameter A); f1) preparing an aqueous suspension of the agglomerates obtained in step d1) and of free magnetic iron material particles; g1) subjecting the aqueous suspension prepared in step f1) to a microwave assisted Fenton process; h1) separating, preferably by filtration, the agglomerates and free magnetic material particles present in the aqueous suspension obtained from step g1), i1) subjecting the agglomerates and free magnetic iron material particles separated in step h1) to a drying step; j1) determining the weight of the dry solid in step i1) to obtain the weight AF (which may also be called parameter AF); k1) subjecting the agglomerates and free magnetic material particles separated in step i1) to a combustion step; and l1) determining the weight of the solid obtained after step k1) and obtaining the weight AFM (which may also be called parameter AFM); Includes. In a second aspect, the present invention relates to a process for determining parameters for the quantification of microplastics in an aqueous matrix comprising microplastics and non-plastic organic particles, and optionally inorganic particles, comprising: a2) providing a first sample of an aqueous matrix comprising microplastics, non-plastic organic particles, and optionally inorganic particles; b2) separating solids from the sample of step a2), preferably by filtration; c2) subjecting the solid separated in step b2) to a drying step; d2) Determine the weight of the dry solid of step c2) and measure the weight ST M (Parameter ST M (which may also be called e2) subjecting the dried solid of step c2) to a combustion step; and f2) Determine the weight of the solid obtained after step e2) and calculate the weight SI M (Parameter SI M (which may also be called g2) providing a second sample of an aqueous matrix comprising microplastics, non-plastic organic particles, and optionally inorganic particles; h2) adding magnetic iron particles to the aqueous matrix provided in step g2) to form microplastic / magnetic iron particle agglomerates and to form non-plastic organic particle / magnetic iron particle agglomerates; i2) separating the formed agglomerates and free magnetic material particles from the mixture of step h2) by applying a magnetic field; j2) preparing an aqueous suspension of the agglomerates separated in step i2) and free magnetic iron material particles; k2) subjecting the aqueous suspension prepared in step j2) to a microwave-assisted Fenton process; l2) separating, preferably by filtration, the agglomerates and free magnetic material particles present in the aqueous suspension obtained from step k2), m2) subjecting the agglomerates and free magnetic iron material particles separated in step l2) to a drying step; n2) Determine the weight of the dry solid in step m2) and calculate the weight STNOX A (Parameter STNOX A (which may also be called o2) subjecting the agglomerates and free magnetic material particles separated in step m2) to a combustion step; p2) Determine the weight of the solid obtained after step o2) and calculate the weight SI A (Parameter SI A (which may also be called q2) filtering the remaining aqueous fraction obtained after the separation of step i2); r2) subjecting the solid separated in step q2) to a drying step; s2) Determine the weight of the dry solid of step r2) and calculate the weight ST SN (Parameter ST SN (which may also be called the t2) subjecting the dried solid of step r2) to a combustion step; u2) Determine the weight of the solid obtained after step t2) and calculate the weight SI SN (Parameter SI SN (which may also be called Includes.

[0025] Since the parameters determined in the first and second aspects correspond to weight (of a solid), these aspects may also be formulated as corresponding processes for determining weight (of a solid).

[0026] In the context of the present invention, the term "microplastic" or "microplastics" refers to plastic material having an average diameter of less than 5 mm, preferably comprised in the range of 0.1 μm to 5 mm, more preferably in the range of 0.1 μm to 1 mm, even more preferably in the range of 0.1 μm to 500 μm, even more preferably in the range of 100 μm to 250 μm. Measuring the size of the microplastic involves its prior separation from the aqueous matrix by vacuum filtration using a microporous membrane filter with a pore size of 0.1 μm or less, and its subsequent drying at room temperature or in a drying oven at a temperature of 100 ° C or less. The filter containing the microplastic is then analyzed by scanning electron microscopy, for example using the conditions described in the examples. The length and width of the microplastic are measured and the size of the largest dimension (length) is assigned. The average diameter is defined as the average length of the microplastic particles (the sum of the lengths of the analyzed particles out of the number of particles analyzed).

[0027] Microplastics can be formed from any plastic material, preferably synthetic organic polymers, such as polyethylene terephthalate (PET), polyethylene (PE), including high density polyethylene (HDPE) and low density polyethylene (LDPE), polyvinyl chloride (PVC), polypropylene (PP), polystyrene (PS), polycarbonate (PC), polyurethane (PU), and combinations thereof.

[0028] "Polyethylene terephthalate" or "PET" is a polymer obtainable by the reaction of polycondensation between terephthalic acid and ethylene glycol. Polyethylene terephthalate has the following structure: [ka]

[0029] "Polyethylene" or "PE" refers to a polymer obtainable by the polymerization of ethylene. Polyethylene has the following structure: [ka]

[0030] "High density polyethylene" or "HDPE" refers to polyethylene whose density falls within the range of 0.930 to 0.970 g / mL. "Low density polyethylene" or "LDPE" refers to polyethylene whose density falls within the range of 0.917 to 0.930 g / mL.

[0031] "Polyvinyl chloride" or "PVC" refers to a polymer obtainable by polymerization of vinyl chloride. Polyvinyl chloride has the following structure: [ka]

[0032] "Polypropylene" or "PP" refers to a polymer obtainable by polymerization of propylene. Polypropylene has the following structure: [ka]

[0033] "Polystyrene" or "PS" refers to a polymer obtainable by polymerization of styrene. Polystyrene has the following structure: [ka]

[0034] "Polycarbonate" or "PC" refers to a polymer containing functional groups linked by carbonate groups (-O-C=O)-O-), such as diallyldiethylene glycol polycarbonate or, most commonly, bisphenol A polycarbonate, the structure of which is shown below. [ka]

[0035] "Polyurethane" or "PU" refers to a polymer obtained by condensation of a polyol, among which ethylene glycol and propylene glycol stand out, with a polyisocyanate, among which methylene diphenyl diisocyanate (MDI) and toluene diisocyanate (TDI), resulting in urethane groups (-NH-(C=O)-O-) in the structure of the polymer. Polyurethanes are widespread due to the range of polyisocyanates and polyols that can be used to form them.

[0036] In a preferred embodiment, the microplastics are selected from the group consisting of polystyrene, polyethylene terephthalate, polyethylene including high and low density polyethylene, polyvinyl chloride, polypropylene, polycarbonate, polyurethane, and mixtures thereof; more preferably, selected from the group consisting of polystyrene, polypropylene, polyethylene terephthalate, polyethylene including high and low density polyethylene, and mixtures thereof; even more preferably, selected from the group consisting of polystyrene, polypropylene, and mixtures thereof; most preferably, polystyrene. An advantage of the process of the present invention is its universal character, since magnetic separation is effective regardless of the chemical nature of the microplastics.

[0037] The expression "aqueous matrix" refers to a composition containing water as its main component, preferably at least 80% by weight, more preferably at least 85%, even more preferably at least 90%, even more preferably at least 95% water relative to the total weight of the composition. The aqueous matrix may further contain other substances already dissolved (e.g. salts such as NaCl) or in suspension. In particular, the aqueous matrix is ​​selected from the group consisting of wastewater (including domestic, urban, industrial, agricultural and livestock breeding wastewater), sea water, river water, lake water, ground water, tap water or mixtures thereof. Thus, among others, wastewater purification plants, drinking water treatment plants, agro-food industries (e.g. fish farms), sources of water for human consumption, water facilities for recreational purposes (e.g. swimming pools) are facilities of interest for applying the process according to the invention. The aqueous matrix comprises microplastics and further comprises non-plastic organic particles. Optionally, the aqueous matrix may further comprise inorganic particles. Thus, in one embodiment, the aqueous matrix comprises microplastics and non-plastic organic particles. In another embodiment, the aqueous matrix comprises microplastics, non-plastic organic particles, and inorganic particles.

[0038] Preferably, the pH of the aqueous matrix should be between 1 and 13, more preferably between 2 and 12, more preferably between 3 and 10, more preferably between 5 and 9, even more preferably between 6 and 8, and most preferably about 7. The pH of the aqueous matrix can be adjusted by adding a base, such as sodium hydroxide, potassium hydroxide or sodium carbonate, among others, or an acid, such as nitric acid, hydrochloric acid or sulfuric acid, among others, until a pH value within the range defined above is reached. The pH can be determined by a pH meter.

[0039] The process of the present invention allows for the separation of microplastics regardless of the electrical conductivity of the water. It is effective for both water with a low level of conductivity of less than 0.05 μS / cm and salt water with a high level of conductivity of 50 mS / cm. The term "electrical conductivity" refers to the ability of any material to conduct electric current. Electrical conductivity can be determined by a conductivity meter.

[0040] Preferably, the concentration of solid particles in suspension in the aqueous matrix should be between 0.1 mg / L and 10000 mg / L, more preferably between 1 mg / L and 2000 mg / L, even more preferably between 10 mg / L and 100 mg / L. The total solid particles in suspension can be determined using processes known to those skilled in the art, for example gravimetric methods based on retaining solid particles on glass fiber filters ("Standard methods for the examination of water and wastewater", "2540 Solids" (APHA, AWWA, WPCF, 1992); Standard UNE-EN 872:2006 Water quality. Determination of solids in suspension. Method by filtration through glass fiber filters).

[0041] Preferably, the solid particles in suspension present in the aqueous matrix are determined as their amount and composition determine the amount of magnetic iron material, preferably magnetite, to be added in the process of the present invention and aid in carrying out the microwave assisted Fenton process of the present invention.

[0042] The process of the present invention requires providing one or more samples of an aqueous matrix containing microplastics. The aqueous matrix also contains non-plastic organic solid particles and may further contain other solids as inorganic particles. In a particular embodiment of the process of the present invention, the aqueous matrix contains inorganic particles. The term "sample" refers to an aliquot, fraction or part of an aqueous matrix having the same qualitative and quantitative composition as the original aqueous matrix. A person skilled in the art knows how to determine the appropriate volume of aqueous matrix sample required to carry out the process of the present invention. Preferably, the volume of the aqueous matrix sample provided in the process of the present invention is between 10 mL and 10 L.

[0043] Steps b1) and h2) comprise the incorporation of magnetic iron particles into the aqueous matrix sample provided for the formation of agglomerates between the microplastics and the magnetic iron particles, which can also form agglomerates with non-plastic organic particles.

[0044] The term "magnetic iron material" refers to any natural or synthetic solid substance that contains at least one iron species and has magnetic properties, i.e., is attracted by a magnet. In preferred embodiments, the magnetic iron material is inorganic. In certain embodiments, the magnetic iron material is uncoated, i.e., bare magnetic material particles. Preferably, the magnetic iron material has a molecular weight of between 5 emu / g and 100 emu / g (5·10 3 A / m and 10 5 A / m), more preferably between 30 emu / g and 90 emu / g (30·10 3 A / m and 90·10 3 A / m), and even more preferably between 65 emu / g and 90 emu / g (65·10 3 A / m and 90·10 3 A / m), most preferably between 70 emu / g and 90 emu / g (70·10 3 A / m and 90·10 3The magnetic properties of the magnetic iron material can be determined using a magnetometer equipped with a SQUID (Superconducting Quantum Interference Device) sensor. The magnetization (M) of the magnetic iron material is measured at room temperature in the range of -10000 to 10000 Oe (corresponding to -797700 to 797700 A / m) depending on the applied external magnetic field (H). The magnetic saturation value of the material is the value of M reached when any subsequent increase in H does not cause an increase in the magnetization of the material. Preferably, the iron material has an iron content of at least 10% by weight, preferably at least 20% by weight, more preferably at least 25% by weight, even more preferably at least 30% by weight, even more preferably at least 35% by weight, even more preferably at least 40% by weight, even more preferably at least 45% by weight, even more preferably at least 50% by weight, even more preferably at least 55% by weight, even more preferably at least 60% by weight, even more preferably at least 65% by weight. The percentage of iron can be determined using a total reflection X-ray fluorescence (TXRF) spectrometer using the method described in the Examples.

[0045] Preferably, the magnetic iron material comprises an iron species selected from the group consisting of Fe(II), Fe(III), metallic Fe, and mixtures thereof. Examples include magnetite (formed by ferrous oxide-ferric oxide FeO·Fe2O3, sometimes formulated as Fe3O4), maghemite (γ-Fe2O3), ilmenite (FeTiO3), and pyrrhotite (Fe 0.8-1 In a preferred embodiment, the magnetic iron material is the mineral magnetite.

[0046] The use of magnetic iron minerals, and in particular magnetite, is advantageous from an economic and environmental standpoint, as it is an abundant, environmentally friendly material that is easily separated from the aqueous matrix.

[0047] The magnetic iron material is in the form of particles. The term "particles" refers to magnetic iron minerals in the form of powders or granules with an average diameter of less than 5 mm, preferably comprised between 0.05 μm and 5 mm, more preferably between 0.05 μm and 1 mm, even more preferably between 0.05 μm and 500 μm, even more preferably between 0.05 μm and 100 μm, even more preferably between 0.1 μm and 10 μm, even more preferably between 0.1 μm and 5 μm, even more preferably between 0.1 μm and 1 μm, even more preferably between 0.1 μm and 0.5 μm, most preferably between 0.1 μm and 0.3 μm. Preferably, the particle size distribution must be sufficiently narrow in the established size range. The determination of the particle size and distribution of the magnetic iron material can be carried out, for example, by scanning electron microscopy using the conditions described in the examples. The length and width of the microplastics are measured and the size of the largest dimension (length) is assigned. The average diameter is defined as the average length of the longest dimension of each magnetic ferrous material particle (the sum of the lengths of the analyzed particles out of the number of particles analyzed). For determining the particle size distribution, it is appropriate to use the statistics D10, D50, and D90, which capture 10%, 50%, and 90% of the accumulated particles by volume. In the preferred range, D10 (indicating that 10% of the particles in the sample by volume have a diameter smaller than this value) is 0.3 μm or less, D50 (indicating that 50% of the particles in the sample by volume have a diameter smaller than this value, representing the average particle size) is 0.50 μm or less, and D90 (indicating that 90% of the particles in the sample by volume have a diameter smaller than this value) is 0.8 μm or less. In the most preferred ranges, D10 (indicating that 10% by volume of the particles of the sample have a diameter smaller than this value) is 0.15 μm or less, D50 (indicating that 50% by volume of the particles of the sample have a diameter smaller than this value, representing the average particle size) is 0.20 μm or less, and D90 (indicating that 90% by volume of the particles of the sample have a diameter smaller than this value) is 0.35 μm or less. The magnetic iron material particles can be obtained by crushing the material and then sieving it into the size ranges mentioned above.The size of the magnetic ferrous material particles refers to the average diameter of the particles determined in dry conditions, without taking into account agglomeration of the magnetic material particles when suspended in an aqueous matrix.

[0048] The term "microplastic / magnetic ferrous particle aggregates" or "microplastic / magnetic ferrous particle aggregates" refers to clusters of particles formed by, preferably due to interactions between, microplastics and magnetic ferrous particles. Similarly, the term "organic particle / magnetic ferrous particle aggregates" or "organic / magnetic ferrous particle aggregates" refers to clusters of particles formed by, preferably due to interactions between, organic particles (non-microplastic) and magnetic ferrous particles. Similarly, the term "non-plastic organic particle / magnetic ferrous particle aggregates" or "non-plastic organic / magnetic ferrous particle aggregates" refers to clusters of particles formed by, preferably due to interactions between, non-plastic organic particles and magnetic ferrous particles. This interaction is a physicochemical interaction; there is an effective fixation between the surfaces of both substances such that the aggregates remain intact despite agitation or modification of the water properties (temperature, pH), but no changes in chemical structure were observed.

[0049] The expression "non-plastic organic particles" or "non-plastic organic solid particles" refers to particles that can have any shape, whose average diameter is in the range of 0.1 μm to 1 cm, preferably 0.1 μm to 5 mm, 0.1 μm to 5 mm, preferably 0.1 μm to 1 mm, more preferably 0.1 μm to 500 μm, even more preferably 100 μm to 500 μm, even more preferably 100 μm to 250 μm, that are not made of plastic material, and whose average diameter is the average length (sum of the lengths of the analyzed particles out of the number of analyzed particles), and whose length is the largest dimension of each particle. Examples of plastics are the same as those described for microplastics. Examples of non-plastic (organic) material particles are of plant origin (leaves, branches, seeds, fruits, etc.), of animal origin (bones, microcrustaceans, larvae, animal remains, etc.), of fungal origin, etc. The size of the particles can be determined in the same way as described for microplastics.

[0050] The expression "inorganic particles" or "inorganic solid particles" refers to particles that can have any shape, whose average diameter is in the range of 0.1 μm to 1 cm, preferably 0.1 μm to 5 mm, preferably 0.1 μm to 5 mm, more preferably 0.1 μm to 1 mm, more preferably 0.1 μm to 500 μm, even more preferably 100 μm to 500 μm, even more preferably 100 μm to 250 μm, are of mineral origin, and whose average diameter is the average length (sum of the lengths of the analyzed particles out of the number of analyzed particles), the length being the largest dimension of each particle. Examples of inorganic particles are sand, clay, insoluble salts, metal oxides, etc. The size of the particles can be determined in the same way as described for microplastics.

[0051] In certain embodiments, the size of the non-plastic organic and inorganic particles is in the same range as the size of the microplastics, preferably all of them having an average diameter of 100 μm to 250 μm.

[0052] In a preferred embodiment, the amount of magnetic iron material particles, preferably magnetite, added to the aqueous matrix in steps b1) and / or h2) (final concentration measured in the aqueous matrix itself) is in the range of 1 mg / L to 4000 g / L, more preferably 10 mg / L to 1000 g / L, even more preferably 10 mg / L to 100 g / L, even more preferably 10 mg / L to 10 g / L and most preferably 100 mg / L to 1 g / L.

[0053] In a particular embodiment, the amount (by weight) of magnetic iron mineral particles, preferably magnetite, added to the aqueous matrix in step b1) should be between 0.1 and 1000 times, more preferably 0.5-500 times, even more preferably 1-100 times, even more preferably 1-70 times, most preferably 1-20 times the amount (by weight) of solid particles in suspension present in the aqueous matrix sample provided in steps a2) and / or g2).

[0054] To determine the amount of magnetic iron material to be added, an aliquot of the aqueous matrix can be taken and the amount of solid particles in suspension in the aqueous matrix can be determined. This involves the application of standardized methods for determining the total solid particles in suspension known to those skilled in the art, such as the gravimetric method based on retaining solid particles on a glass fiber filter ("Standard methods for the examination of water and wastewater", "2540 Solids" (APHA, AWWA, WPCF, 1992); Standard UNE-EN 872:2006 Water quality. Determination of solids in suspension. Method by filtration through glass fiber filters). Generally, in this method, a sample of an aqueous matrix of known volume is filtered using a device under vacuum or low pressure through a glass fiber filter with a pore size of 0.45 μm; the filter containing the retained solid particles is subsequently dried at 105° C. and the mass of the retained solids is determined by weight difference relative to the clean filter. The concentration of the total solid particles in the suspension can be obtained by dividing the result obtained by the volume of the filtered aqueous matrix. To determine the solid particles in the suspension, the filter containing the retained solid particles and dried at 105°C is subjected to combustion at 550°C for at least 1 hour until a constant mass value is reached. The concentration of inorganic solid particles in the suspension can be obtained by dividing the final mass value by the volume of the filtered aqueous matrix. The concentration of organic solid particles in the suspension (volatile solids) is determined by the difference in concentration between the total solid particles in the suspension and the inorganic solid particles in the suspension (non-volatile solids).

[0055] All or a portion of the non-plastic organic particles present in the aqueous matrix form aggregates with the magnetic ferrous material. Preferably, at least 50% by weight, more preferably at least 60%, even more preferably at least 70%, even more preferably at least 80%, even more preferably at least 85%, even more preferably at least 90%, even more preferably at least 95%, even more preferably at least 98%, even more preferably at least 99%, and even more preferably 100% of the non-plastic organic particles form aggregates with the magnetic ferrous material, based on the total weight of the non-plastic organic particles present in the aqueous matrix.

[0056] Preferably, at least 90% by weight of the microplastics, based on the total weight of the microplastics present in the aqueous matrix, more preferably at least 95%, even more preferably at least 98%, even more preferably at least 99%, and even more preferably 100% of the microplastics form aggregates with the magnetic iron material.

[0057] In a preferred embodiment, the mixture obtained in step b1) and / or h2) is subjected to stirring before carrying out step c1) and / or j2), respectively. The stirring promotes the interaction of the magnetic iron material particles with the particles in suspension present in the aqueous matrix (including microplastics), resulting in the formation of agglomerates (microplastics / magnetic iron material and non-plastic organic particles / magnetic iron material). The stirring can be carried out by any conventional method known to the person skilled in the art, for example mechanical, magnetic or electrostatic stirring, more preferably mechanical stirring.

[0058] Once agglomerates are formed between the particles in suspension contained in the aqueous matrix (including microplastics and non-plastic organic particles) and the magnetic iron material, these agglomerates are separated from the aqueous matrix together with the free magnetic iron material by applying a magnetic field in steps c1) and / or i2).

[0059] The magnetic field can be generated by means of a magnet or an electromagnet, preferably by means of a magnet.

[0060] The process of the present invention has the added advantage of the simplicity of the equipment required.

[0061] In the process of the first aspect, the agglomerates and free magnetic iron material particles separated in step c1) are subjected to a drying step. The drying can be carried out by any method suitable for removing the waste water present and not degrading the microplastics, preferably by subjecting the separated solids (agglomerates and free magnetic iron material particles) to a temperature of 100-200° C., preferably 100-150° C., more preferably 100-110° C., even more preferably about 105° C. The drying temperature is preferably maintained for 1 hour to 3 hours, more preferably 1.5 hours to 2.5 hours.

[0062] Next, in the process of the first aspect, step e1) is performed to determine the weight of the dry solids of step d1), thereby obtaining weight A (which may also be referred to as parameter A). Weight A (or parameter A) is thus the weight of the dry solids determined in step e1).

[0063] The next steps of the process of the invention, steps f1) and j2), concern the preparation of an aqueous suspension of previously separated, and in the case of the first embodiment previously dried, particle agglomerates (both microplastic and non-plastic organic particles) and free magnetic iron material particles.

[0064] In a preferred embodiment, the volume of water used to resuspend the aggregates and free magnetic iron material particles is in the range of 1 mL to 1000 mL, more preferably 10 mL to 500 mL, even more preferably 10 mL to 250 mL, and most preferably 10 mL to 100 mL.

[0065] The next steps of the process of the invention, steps g1) and k2), consist in selectively oxidizing the previously separated non-plastic organic particles (which are in the form of agglomerates with the magnetic iron material) without affecting the chemical and structural integrity of the microplastics also present in the separated microplastic / magnetic iron material agglomerates.

[0066] In a preferred embodiment, the selective oxidation of non-plastic organic particles (forming agglomerates with magnetic iron materials) is carried out by applying the microwave assisted Fenton process.

[0067] In a preferred embodiment, the pH of the aqueous suspension of steps f1), g1), j2) and k2) is adjusted to be in the range of 2 to 5, more preferably between 2 and 4, more preferably between 2.5 and 3.5, most preferably about 3. The pH of the aqueous suspension can be adjusted by adding an acid, such as, inter alia, nitric acid, hydrochloric acid or sulfuric acid, until a pH value within the range defined above is reached. Preferably, nitric acid is used. The pH can be determined by a pH meter.

[0068] The selective oxidation of non-plastic organic particles in the microwave-assisted Fenton process requires the addition of hydrogen peroxide and salts of transition metals such as Fe, Cu, Mn and Co to the previous aqueous suspension. Preferably, the added salt from the previous group is an Fe salt. Preferably, an iron salt selected from the group consisting of iron nitrate, iron chloride, iron sulfate and mixtures thereof, preferably iron nitrate, is used as the precursor of iron in the solution.

[0069] In a preferred embodiment, the amount of iron added is the amount necessary to provide a final dissolved iron concentration in the aqueous suspension of step e) itself; in the range of 1 mg / L to 1000 mg / L, more preferably 1 mg / L to 100 mg / L, even more preferably 5 mg / L to 100 mg / L, most preferably 10 mg / L to 100 mg / L.

[0070] In a preferred embodiment, the amount of dissolved iron (by weight) added to the aqueous suspension of steps g1) and k2) is 0.01-5 times, more preferably 0.1-2 times, even more preferably 0.5-2 times, most preferably 0.5-2 times the amount (by weight) of organic particles, including microplastics and non-plastic organic particles as defined above, present in the aqueous matrix sample provided in steps a1) and g2), respectively. To determine the amount of dissolved iron added, an aliquot of the aqueous matrix can be taken and the amount of solid particles in suspension in the aqueous matrix can be determined. This includes the application of standardized methods for determining the total solid particles in suspension known to those skilled in the art, such as gravimetric methods based on retaining solid particles on glass fiber filters ("Standard methods for the examination of water and wastewater", "2540 Solids" (APHA, AWWA, WPCF, 1992); Standard UNE-EN 872:2006 Water quality. Determination of solids in suspension. Method by filtration through glass fiber filters). Generally, in this method, a sample of an aqueous matrix of known volume is filtered using a device under vacuum or low pressure through a glass fiber filter with a pore size of 0.45 μm; the filter containing the retained solid particles is subsequently dried at 105 ° C and the mass of the retained solids is determined by weight difference relative to the clean filter. The concentration of the total solid particles in the suspension can be obtained by dividing the result obtained by the volume of the filtered aqueous matrix. To determine the inorganic and organic solid particles in the suspension, the filter containing the retained solid particles and dried at 105 ° C is subjected to combustion at 550 ° C for at least 1 hour until a constant mass value is reached. The concentration of the inorganic solid particles in the suspension can be obtained by dividing the final mass value by the volume of the filtered aqueous matrix. The concentration of the organic solid particles in the suspension (volatile solids) is determined by the difference in concentration between the total solid particles in the suspension and the inorganic solid particles in the suspension (non-volatile or fixed solids).

[0071] In a preferred embodiment, the amount of hydrogen peroxide added to the aqueous suspension of steps g1) and k2) is the amount necessary to provide a final concentration, measured in the aqueous suspension itself, in the range of 10 mg / L to 100 g / L, more preferably 10 mg / L to 50 g / L, even more preferably 100 mg / L to 50 g / L, even more preferably 100 mg / L to 25 g / L, even more preferably 1 g / L to 25 g / L, and most preferably 1 g / L to 10 g / L.

[0072] In a preferred embodiment, the amount of hydrogen peroxide (by weight) added to the aqueous suspension of steps g1) and k2) is 1-10000 times, more preferably 10-1000 times, even more preferably 100-1000, and most preferably 100-500 times the amount of organic solid particles, including microplastic and non-plastic organic particles, present in the aqueous matrix sample provided in steps a1 and g2), respectively. To determine the amount of hydrogen peroxide to be added, an aliquot of the aqueous matrix can be taken and the amount of organic particles, including microplastic and non-plastic organic particles, in the aqueous matrix can be determined. This includes the application of standardized methods for determining the total solid particles in a suspension known to those skilled in the art, such as gravimetric methods based on retaining solid particles on glass fiber filters ("Standard methods for the examination of water and wastewater", "2540 Solids" (APHA, AWWA, WPCF, 1992); Standard UNE-EN 872:2006 Water quality. Determination of solids in suspension. Method by filtration through glass fiber filters). In general, in this method, a sample of an aqueous matrix of known volume is filtered using a device under vacuum or low pressure through a glass fiber filter with a pore size of 0.45 μm; subsequently, the filter containing the retained solid particles is dried at 105 ° C and the mass of the retained solids is determined by weight difference relative to the clean filter. The concentration of the total solid particles in the suspension can be obtained by dividing the obtained result by the volume of the filtered aqueous matrix. To determine the inorganic and organic particles in the suspension, including microplastics and non-plastic organic particles, the filter containing the retained solid particles and dried at 105 ° C is subjected to combustion at 550 ° C for at least 1 hour until a constant mass value is reached. The concentration of the inorganic solid particles can be obtained by dividing the final mass value by the volume of the filtered aqueous matrix. The concentration of the organic particles is determined by the difference in concentration between the total particles in the suspension and the inorganic particles in the suspension.

[0073] In a particular embodiment, both the iron salt and hydrogen peroxide are added in one addition at the start of the oxidation reaction of steps g1) and k2).

[0074] Preferably, the process of the present invention is carried out by adding iron salt and hydrogen peroxide during steps g1) and k2) in several successive cycles to facilitate the reaction.

[0075] Each time iron and hydrogen peroxide reagents are added to the aqueous suspension during steps g1) and k2), the aqueous suspension is introduced into a microwave to carry out the selective oxidation reaction.

[0076] In a preferred embodiment, the microwave power is in the range of 50-1500W, more preferably 500-1200W, even more preferably 600-1100W, and most preferably 700-1000W.

[0077] In a preferred embodiment, the reaction time for carrying out the selective oxidation of non-plastic organic solid particles by microwave-assisted Fenton in steps g1) and k2) is in the range of 1 second to 2 hours, more preferably 1 second to 1 hour, even more preferably 1 second to 30 minutes, even more preferably 1 second to 10 minutes, and most preferably 2 minutes to 5 minutes. The reaction time refers to the total oxidation time, and the oxidation can be carried out either by two or more shorter cycles, for example 2, 3, 4, 5, or 6 cycles, or all in one shot.

[0078] In a preferred embodiment, the temperature of the sample during the microwave-enhanced Fenton reaction reaches at least 80°C, preferably 80-120°C, more preferably 90-100°C.

[0079] The next steps of the process of the present invention, steps h1) and l2), are the separation, preferably by filtration, more preferably by vacuum filtration, of the agglomerates and free magnetic material particles present in the aqueous suspension resulting from steps g1) and k2), respectively.

[0080] The next steps of the process of the invention, steps i1) and m2), are to subject the agglomerates and free magnetic iron material particles separated in steps h1) and l2), respectively, to a drying step. The drying can be carried out by any method suitable for removing any waste water present, preferably by subjecting the separated solids to a temperature of 100-200° C., preferably 100-150° C., more preferably 100-110° C., even more preferably about 105° C. The drying temperature is preferably maintained for a period of 1 hour to 3 hours, more preferably 1.5 hours to 2.5 hours.

[0081] Next, in the process of the first embodiment, step j1) is performed to determine the weight of the dry solid of step i1), thereby obtaining the weight AF (which may also be called parameter AF), while in the process of the second embodiment, step n2) is performed to determine the weight of the dry solid of step m2), thereby obtaining the weight STNOX A (Parameter STNOX A Thus, the weight AF (or parameter AF) is the weight of the dry solids determined in step j1), and the weight STNOX A (or parameter STNOX A ) is the weight of dry solids determined in step n2).

[0082] The process of the invention then, in steps k1) and o2), respectively, subjects the agglomerates and the free magnetic material particles separated in steps i1) and m2) to a combustion step. Preferably, the combustion is carried out in an air atmosphere. Preferably, the combustion is carried out by a treatment at a temperature of 400-600°C, more preferably 500-600°C, even more preferably about 550°C. In particular, this treatment lasts for 1-4 hours, preferably 1-3 hours, more preferably 1.5-2.5 hours, most preferably about 2 hours. This treatment ensures the combustion of any plastic material present in the sample. This treatment does not affect inorganic particles, which may optionally be present, or magnetic ferrous materials. The combustion step removes the organic particles present in the agglomerates.

[0083] In the process of the invention, steps l1) or p2) are then carried out to determine the weight of the solid particles obtained after the combustion steps k1) and o2), respectively. Thus, in the process according to the first aspect of the invention, the weight AFM (which may also be called the parameter AFM) is obtained, whereas in the process according to the second aspect of the invention, the weight SI A (Parameter SI A The weight AFM (or parameter AFM) is thus the weight of the solid particles determined in step l1), and the weight SI A (or parameter SI A ) is the weight of the solid particles determined in step p2).

[0084] All measurements of the weight of solids are preferably carried out after the corresponding solids have been cooled to 10-35°C, more preferably 20-25°C.

[0085] The second aspect of the invention further comprises the additional steps a2) to f2) and q2) to u2).

[0086] Steps a2) to f2) are performed on a sample of aqueous matrix containing microplastics, non-plastic organic particles and optionally inorganic particles which is different to the sample used in steps g2) to p2) above, although both samples originate from the same aqueous matrix.

[0087] Step a2) refers to providing a sample of an aqueous matrix containing microplastics, non-plastic organic particles, and optionally inorganic particles, as defined above for steps a1) and g2).

[0088] Step b2) refers to the separation of solids from the sample of step a2), preferably by filtration, more preferably by vacuum filtration.

[0089] Step c2) refers to subjecting the solid separated in step b2) to a drying step, which is as defined above for steps d1), i1) and m2).

[0090] Step d2) refers to the determination of the weight of the dry solid of step c2), weight ST M (Parameter ST M Therefore, we obtain the weight ST M (or parameter ST M ) is the weight of dry solids determined in step d2).

[0091] Step e2) refers to subjecting the dried solid of step c2) to a combustion step, which is as defined above for steps k1) and o2).

[0092] Step f2) refers to the determination of the weight of the solid obtained after step e2), the weight SI M (Parameter SI M Therefore, we obtain the weight SI M (or parameter SI M ) is the weight of solids determined in step f2).

[0093] Steps g2) to u2) are carried out on the same sample of aqueous matrix containing microplastics, non-plastic organic particles and optionally inorganic particles used in steps g2) to p2) above; they are a continuation of the processing of said sample as described in steps g2) to p2).

[0094] Step q2) refers to the filtration, preferably vacuum filtration, of the remaining aqueous fraction obtained after the separation of step i2).

[0095] Step r2) refers to subjecting the solid separated in step q2) to a drying step, which is as defined above for steps d1), i1) and m2).

[0096] Step s2) relates to the determination of the weight of the dry solid of step r2), weight ST SN (Parameter ST SN Therefore, we obtain the weight ST SN (or parameter ST SN) is the weight of dry solids determined in step s2).

[0097] Step t2) refers to subjecting the dried solid of step r2) to a combustion step, which is as defined above for steps k1) and o2).

[0098] Step u2) refers to the determination of the weight of the solid obtained after step t2), the weight SI SN (Parameter SI SN Therefore, we obtain the weight SI SN (or parameter SI SN ) is the weight of solids determined in step u2).

[0099] Process for quantification of microplastics In a third aspect, the present invention relates to a process for the quantification of microplastics in an aqueous matrix comprising microplastics and non-plastic organic particles, and optionally inorganic particles, the process comprising: I-1) carrying out steps a1) to l1) of the process for determining parameters according to the first embodiment for determining the weights A, AF and AFM (which may also be referred to as parameters A, AF and AFM); II-1) Weight of microplastics (MP A ) to calculate:

[0100]

number

[0101] During the ceremony, A is the weight of solids determined in step e1) of the process according to the first aspect, AFM is the weight of solids determined in step l1) of the process according to the first embodiment, MO NP,A is calculated using Equation 2,

[0102]

number

[0103] where A is the weight of solids determined in step e1) of the process according to the first aspect, AF is the weight of solids determined in step j1) of the process according to the first aspect and a is a number between 0.7 and 1, preferably between 0.8 and 0.9, most preferably 0.8.

[0104] The process of the third aspect comprises a first step I-1 for determining a parameter relevant for the quantification of microplastics (i.e. weight), which comprises carrying out the process defined in the first aspect.

[0105] A, AFM, and AF must be expressed in the same units of weight.

[0106] The process of the third embodiment also includes a second step II-1 of calculating the weight of microplastics. This step is carried out using Equation 1 and Equation 2. Nevertheless, the process is not limited to said equations, but rather encompasses any mathematically equivalent equation or mathematical combination of said equations.

[0107] In a fourth aspect, the present invention relates to a process for the quantification of microplastics in an aqueous matrix comprising microplastics and non-plastic organic particles, and optionally inorganic particles, the process comprising:

[0108] I-2) Weight ST M、 SI M , STNOX A , S.I. A , S.T. SN , and S.I. SN (Parameter ST M、 SI M , STNOX A , S.I. A , S.T. SN , and S.I. SNperforming steps a2) to u2) of the process for determining a parameter according to the second aspect for determining a parameter; II-2) Weight of microplastics (MP M ) to calculate:

[0109]

number

[0110] During the ceremony, %MP is calculated using Equation 4:

[0111]

number

[0112] where RMPSO is calculated using Equation 5:

[0113]

number

[0114] where a is a number between 0.7 and 1, preferably between 0.8 and 0.9, and most preferably 0.8; and PPSO is calculated using Equation 6:

[0115]

number

[0116] During the ceremony, STNOX A is the weight of the solids determined in step n2) of the process according to the second embodiment, SI A is the weight of solids determined in step p2) of the process according to the second embodiment, and SO A is calculated using Equation 7,

[0117]

number

[0118] In the formula, SI A is the weight of solids determined in step p2) of the process according to the second embodiment, SI SN is the weight of solids determined in step u2) of the process according to the second embodiment, ST SN is the weight of solids determined in step s2) of the process according to the second aspect, M is the weight of magnetic material particles added in step h2) of the process according to the second aspect, ST M is the weight of solids determined in step d2) of the process according to the second embodiment, SI M is the weight of solids determined in step f2) of the process according to the second embodiment.

[0119] The process of the fourth aspect comprises a first step I-2 of determining a parameter (i.e. weight) relevant for the quantification of microplastics, which comprises carrying out the process defined in the second aspect.

[0120] Weight ST M、 SI M , STNOX A , S.I. A , S.T. SN , and S.I. SN must be expressed in the same units of weight.

[0121] The process of the fourth embodiment also includes a second step II-2 of calculating the weight of microplastics. This step is carried out using Equations 3-7. Nevertheless, the process is not limited to said equations, but rather encompasses any mathematically equivalent equation or mathematical combination of said equations.

[0122] Illustrative examples are set forth below to disclose the features and advantages of the present invention, but they should not be construed as limiting the scope of the invention as defined in the claims. EXAMPLES

[0123] Materials and Methods Determining the particle size and shape of microplastics In the present invention, microplastics were added to an aqueous matrix and then subjected to magnetic separation by the process described herein. The particle size range of the microplastics was pre-determined by sieving using different size sieves (5 mm, 1 mm, 500 μm, 250 μm, 100 μm, 50 μm, 20 μm).

[0124] Measuring the size of microplastics in a real aqueous matrix involves their prior separation from the aqueous matrix by vacuum filtration using a microporous membrane filter with a pore size of 0.1 μm or less, and their subsequent drying at room temperature or in a drying oven at a temperature of 100 °C or less. The filters containing the microplastics are then analyzed by optical microscopy. In this case, a Nikon Eclipse Ci-S / Ci-L upright optical microscope equipped with a DS-Fi2 digital camera and a DS-U3 control unit, with software for measuring and processing the images (NIS-Elements L Imaging), was used. A JEOL JSM 6335F scanning electron microscope with amplification from 10x to 500,000x was also used. The length and width of the microplastics are measured and the size of the largest dimension (length) is assigned. The shape of the microplastics is analyzed by observing images of the particles at different magnifications.

[0125] Determining the composition of microplastics The composition of the microplastics was determined by Fourier transform infrared spectroscopy (FTIR). The microplastic samples were analyzed according to the conventional analytical method using KBr pellets. Pellets were prepared by adding 1 mg of the microplastic sample and approximately 99 mg of KBr. The resulting powder mixture was compressed by applying a pressure of 10 tons by a hydraulic press to obtain KBr pellets. The samples were then analyzed using a Spectrum Two spectrophotometer (Perkin Elmer). The transmission test was performed at 4000-450 cm -1The spectra obtained were compared to a library database to determine the type of polymer forming the microplastics using Perkin Elmer Spectrum Software.

[0126] Determination of particle size of magnetic ferrous materials The particle size (mean diameter) and particle distribution of the magnetic ferrous material were determined by scanning electron microscopy analysis of the dry material. The instrument used was a JEOL JSM 6335F with amplification from 10x to 500,000x. The length and width of the magnetic ferrous material particles were measured and assigned a size of the largest dimension (length). The statistics D10, D50, and D90, which capture 10%, 50%, and 90% of the accumulated particles by volume, are appropriate for determining the particle size distribution.

[0127] Determination of iron percentage The iron content of the magnetic ferrous material was determined using a total reflection X-ray fluorescence (TXRF) spectrometer, i.e., S2 Peakfox (Bruker) model equipped with a molybdenum source. The sample preparation method consisted of open vessel digestion of the sample with a solution of hydrochloric, nitric and hydrofluoric acids in a volume ratio of 6:2:0.5 at 105 °C for 1.5 hours. The concentration of the material in the vessel was 1000 mg / L and a total volume of 10 mL was used. If necessary, the magnetic ferrous material was pre-ground to a size of less than 100 μm. Once the material sample was digested, an internal gallium standard was added to the solution for later quantification. A 3 μL aliquot of the resulting solution was introduced into the analytical spectrometer and run at 50 kV and 600 μA with an acquisition time of 500 seconds. Integration of the peak corresponding to iron in the resulting spectrogram allowed the weight percentage of iron contained in the material to be determined.

[0128] X-ray diffraction Identification and characterization of the crystalline phases present in the magnetic iron material was performed using powder X-ray diffraction (PXRD). Samples were analyzed on a Panalytical X'Pert PRO theta / theta diffractometer equipped with a Cu tube (Kα radiation, 8.04 keV). The diffractometer has a secondary graphite monochromator and a Xe gas detector. Theta / 2theta scans were performed in the 2θ range of 10-80°, with an angle increment of 0.04°, and an accumulation time of 4 seconds. Prior to analysis, magnetic iron material particles were milled to a size of less than 100 μm, if necessary. High Score Plus software and the ICDD (International Centre for Diffraction Data) PDF-4 Full File crystallography database were used to identify the crystalline phases present in the obtained diffractograms.

[0129] Determining magnetic saturation The magnetic properties of the magnetic iron materials were measured using a Quantum Design MPMS XL-5 magnetometer equipped with a SQUID (Superconducting Quantum Interference Device) sensor. If necessary, the magnetic iron materials were pre-ground to a size smaller than 100 μm. The magnetic moment (M) of the magnetic iron materials is −10,000 to 10,000 Oe (−797,700 to 797,700 A m in SI) at room temperature. -1 The magnetic saturation value is the value of M reached when any subsequent increase in H does not cause an increase in the magnetization of the material.

[0130] Determination of total fixed and volatile particles in suspension Generally, in this work, the determination of particles in suspension was carried out by the method described in the standard UNE-EN 872 for the determination of particles in suspension using vacuum filtration. In that sense, a known volume of the aqueous matrix to be analyzed was filtered through a glass fiber filter of known weight using a device under vacuum or low pressure. The filter containing the retained particles was subsequently dried at 105°C and the particle mass was determined by weight difference with respect to the original filter. In the described example, the vacuum filtration was carried out using a microporous membrane filter with a pore size of 0.45 μm. The filter with the solids was then dried in a drying oven at 105°C for 2 hours. Once dry and cooled, the filter containing the solids was weighed on a precision scale and the mass of the total solids (ST M ) was determined by weight difference for the same filter. M ) and volatile solid particles in suspension (organic matter, SO M To determine the mass of the solid particles, the filter containing the retained and dried solid particles at 105°C is subjected to combustion at 550°C for at least 1 hour until a constant mass value is reached. Upon cooling, the filter containing the solids is weighed on a precision scale and the mass of the total solids fixed solid particles in suspension is determined by weight difference against the same filter. The mass of the volatile solid particles in suspension is determined by the difference between the mass of the total solids and the mass of the volatile solids.

[0131] In the oxidation experiments carried out, the degree of removal of organic solid particles present in the different samples was calculated. In that sense, the removal rate of organic solid particles in suspension is calculated as the mass of solid particles in suspension (SS) present in the sample to be oxidized. 初期 ) and the mass of solid particles in the suspension determined after the oxidation process (SS 最終 ) was calculated (Equation 8).

[0132]

number

[0133] Example 1. Effect of the presence of other non-plastic organic solid particles on the partitioning of polystyrene microplastics in a synthetic aqueous matrix Polystyrene microplastic separation experiments were carried out using an aqueous matrix to which was added non-plastic organic solid particles with a similar size to the microplastics. The separation process was carried out using a magnetic iron mineral, namely ground magnetite (with an average particle diameter of 0.2 μm under dry conditions and the particle size distribution shown in Figure 1). The crystalline character of the magnetite used was confirmed by X-ray diffraction analysis, which also showed that the only phase present in the solid was magnetite (Fe3O4). The percentage of iron in the magnetic minerals used was in the range of 68-78% by weight. In turn, the magnetic saturation values ​​of the materials were in the range of 70-90 emu / g, which is 70·10 in SI units. 3 ~90·10 3 Corresponds to A / m.

[0134] The experiments were carried out in glass vials into which the aqueous matrix, microplastics, non-plastic organic solid particles, and magnetite particles were introduced. The solid particles (microplastics, non-plastic organic solid particles, and magnetite particles) remained in suspension in the aqueous matrix. The conductivity and pH values ​​were measured using a conductivity meter and a pH meter, respectively. All tests were carried out using an aqueous matrix with a salt (sodium chloride) concentration of 0.1 g / L and a pH value of 7. All experiments were carried out in triplicate.

[0135] The volume of the aqueous matrix used was 50 mL and the amount of polystyrene microplastics added was 10 mg. In each test, 10 mg of one of the selected types of non-plastic organic solid particles with the same size range as the size range of the microplastics (all solids were sieved using a sieve with the mesh opening diameter in the size range of 100-250 μm) and 20 mg of magnetic iron mineral particles were added to the suspension. The nature of the added non-plastic solid particles was varied by using organic particles (flour, crustacean exoskeletons, bivalve shells, pine needles, elm leaves, mimosa leaves, cellulose). The suspension was then mechanically stirred for 30 seconds using a paddle stirrer. A magnetic field generated by a magnet was then applied to separate the magnetic solids (free magnetic iron minerals and aggregates formed between magnetic iron minerals and microplastics or non-plastic organic solid particles) from the aqueous matrix. Table 1 includes the sizes of the microplastics and magnetic minerals studied, the amounts of magnetite and microplastics added, the nature and amount of non-plastic organic solid particles in suspension added, and the yields achieved in the separation, both for the separation of microplastics and for the separation of non-plastic organic solid particles in suspension.

[0136] [Table 1]

[0137] The separation of polystyrene microplastics was very efficient, achieving a recovery rate of more than 99.0%. It should be pointed out that no difference in the separation yield of polystyrene microplastics due to the presence of other non-plastic organic solid particles in suspension in the aqueous matrix was observed. However, the yields in the separation of the particles actually differed considerably based on their nature. In that sense, crustacean exoskeletons, pine needles, elm leaves, and mimosa leaves, as well as cellulose, were separated with a yield similar to that of microplastics, although some, such as flour, were separated with a lower yield. These results confirm that microplastics are effectively separated from the matrix, regardless of the content of non-plastic organic solid particles in the suspension of the water analyzed. However, it is very likely that non-plastic organic particles in the suspension are also magnetically extracted from the matrix with a high yield, which requires subsequent oxidation to isolate the microplastics.

[0138] Leaching of iron from magnetic iron minerals during separation experiments was essentially negligible (<0.1 mg / L) regardless of the solids in suspension added to the aqueous matrix.

[0139] Example 2. Application of microwave-assisted Fenton process for the selective oxidation of non-plastic organic solid particles magnetically separated together with microplastics from a synthetic aqueous matrix

[0140] The oxidation experiment of non-plastic organic solid particles was carried out after the experiment of magnetic separation of said particles in the presence of polystyrene microplastics, as shown in Example 1. The magnetic separation of solid particles was carried out by adding 50 mg of non-plastic organic solid particles (ground pine needles sieved in the size range of 100-250 μm (using a sieve with said mesh opening diameter), 10 mg of polystyrene microplastics (100-250 μm), and 60 mg of magnetic iron mineral to a volume of 50 mL of water. The magnetic iron mineral used in the process of magnetic separation was ground magnetite, which has an average particle diameter of 0.2 μm under dry conditions and a particle size distribution shown in Figure 1. The crystalline characteristics of the magnetite used were confirmed by X-ray diffraction analysis, which also showed that the only phase present in the solid was magnetite (Fe3O4). The percentage of iron in the magnetic mineral used was in the range of 68-78% by weight. The magnetic saturation value of the material was then in the range of 70-90 emu / g, which is 70·10 in SI units. 3 ~90·10 3 Corresponds to A / m.

[0141] The suspension was then mechanically stirred for 1 minute using a paddle stirrer, resulting in the formation of magnetic iron mineral / microplastic aggregates and magnetic iron mineral / non-plastic organic solid particle aggregates. A magnetic field generated by a magnet was then applied to magnetically separate the formed aggregates and excess magnetic iron mineral from the aqueous matrix.

[0142] The magnetic separation yield of both non-plastic organic solid particles (pine needles) and polystyrene microplastics (due to aggregate formation) was greater than 99.0%. The magnetically separated fraction was then subjected to a microwave-assisted Fenton oxidation process with the aim of selectively removing the non-plastic organic solid particles, thus allowing the microplastic concentration to be quantified.

[0143] The oxidation experiments of the non-plastic organic solid particles present in the separated magnetic fraction were carried out by resuspending said fraction in a volume of 50 mL of aqueous matrix. The oxidation reaction was carried out in a glass Erlenmeyer flask into which the aqueous matrix and the previously separated magnetic fraction (formed by magnetite / microplastic aggregates, magnetite / non-plastic organic solid particle aggregates and free magnetite) were introduced.

[0144] The solids forming the magnetic fraction separated in the previous step remained in suspension in the aqueous matrix. The pH of the aqueous matrix was adjusted to 3 using nitric acid. The pH value was measured using a pH meter. All experiments were carried out in triplicate. Iron in solution (1 mL of concentrated solution prepared using iron nitrate nonahydrate (Fe(NO3)3*9H2O) to reach a final concentration of 10 mg / L in the reaction medium) was added to the suspension as a catalyst, as was hydrogen peroxide (1 mL of concentrated solution to reach a final concentration in the medium of 5 g / L). Immediately after the reagents were added, the Erlenmeyer flask was introduced into a microwave (Teka, MW 225G model, frequency 2450 MHz) with a power of 700 W, corresponding to 55% of the maximum microwave power. Every 2 minutes, the flask was removed from the microwave and the reagents (iron and hydrogen peroxide) were added again, and this process was repeated for a total of up to 5 consecutive cycles.

[0145] Once the oxidation experiment was completed, the content of solid particles in the suspension was determined, and the removal yield of organic solid particles was calculated by the difference relative to the amount of solids initially present (microplastics, non-plastic organic solid particles, and magnetite added) (Equation 1).

[0146] Table 2 contains the results obtained in the removal of non-plastic organic solid particles in suspension in the presence of polystyrene microplastics.

[0147] [Table 2]

[0148] The oxidation of non-plastic organic solid particles by microwave-assisted Fenton process with the addition of iron and hydrogen peroxide in 5 cycles lasting 2 min in duration was very efficient in the presence of magnetite, achieving a removal yield of about 90% of the particles. It is also important to emphasize that polystyrene microplastics are not affected by the oxidation treatment, and their mass is practically intact at the end of the reaction, even though they have the same size as the non-plastic organic solid particles. Moreover, the composition and size of the microplastics also did not persist significantly after the treatment. These results clearly demonstrate the suitability of the developed oxidation process to isolate microplastics in an aqueous matrix containing other non-plastic organic solid particles in suspension, even when they form part of the aggregates together with magnetite.

[0149] Example 3. Application of microwave-assisted Fenton process for selective oxidation of non-plastic organic solid particles magnetically separated together with microplastics from real aqueous matrices

[0150] Experiments on the oxidation of non-plastic organic solid particles present in real aqueous matrices were carried out after experiments on the magnetic separation of said solids in the presence of polystyrene microplastics. For each of the real aqueous matrices evaluated, 100 mg of polystyrene microplastics (100-250 μm) and 400 mg of magnetic iron mineral in a volume of 1 L were used. River water, secondary treatment effluent from a wastewater treatment plant and tertiary treatment effluent were used as aqueous matrices. The separation process was carried out using a magnetic iron mineral, namely crushed magnetite (having a mean particle diameter of 0.2 μm under dry conditions and the particle size distribution shown in Figure 1). The crystalline nature of the magnetite used was confirmed by X-ray diffraction analysis, which also showed that the only phase present in the solid was magnetite (Fe3O4). The percentage of iron in the magnetic mineral used was in the range of 68-78% by weight. The magnetic saturation value of the material was then in the range of 70-90 emu / g, which corresponds to 70·10 in SI units. 3 ~90·10 3Corresponds to A / m.

[0151] The suspension was then mechanically stirred for 30 seconds using a paddle stirrer, resulting in the formation of magnetic iron mineral / microplastic aggregates and magnetic iron mineral / non-plastic organic solid particle aggregates. A magnetic field generated by a magnet was then applied to magnetically separate the formed aggregates and excess magnetic iron mineral from the aqueous matrix.

[0152] For both non-plastic organic solid particles and incorporated polystyrene microplastics present in the real aqueous matrix, magnetic separation (due to aggregate formation) achieved yields of more than 95.0%. The magnetically separated fraction was then subjected to a microwave-assisted Fenton oxidation process with the aim of selectively removing the organic solids, thus allowing the microplastic concentration to be quantified.

[0153] The oxidation experiments of the non-plastic organic solid particles present in the separated magnetic fraction were carried out by resuspending said fraction in a volume of 50 mL of aqueous matrix. The oxidation reaction was carried out in a glass Erlenmeyer flask into which the aqueous matrix and the previously separated magnetic fraction (formed by magnetite / microplastic aggregates, magnetite / non-plastic organic solid particle aggregates and free magnetite) were introduced.

[0154] The solids forming the magnetic fraction separated in the previous step remained in suspension in the aqueous matrix. The pH of the aqueous matrix was adjusted to 3 using nitric acid. The pH value was measured using a pH meter. All experiments were carried out in triplicate. Iron in solution (1 mL of concentrated solution prepared using iron nitrate nonahydrate (Fe(NO3)3*9H2O) to reach a final concentration of 10 mg / L in the reaction medium) was added to the suspension as a catalyst, as was hydrogen peroxide (1 mL of concentrated solution to reach a final concentration in the medium of 5 g / L). Immediately after the reagents were added, the Erlenmeyer flask was introduced into a microwave (Teka, MW 225G model, frequency 2450 MHz) with a power of 700 W, corresponding to 55% of the maximum microwave power. Every 2 minutes, the flask was removed from the microwave and the reagents (iron and hydrogen peroxide) were added again, and this process was repeated for a total of up to 5 consecutive cycles.

[0155] Once the oxidation experiment was completed, the content of solids in the suspension was determined and the removal yield of organic solid particles was calculated by the difference with respect to the amount of solids initially present in the aqueous matrix (added microplastics and magnetite together with non-plastic organic solid particles) (Equation 8).

[0156] Table 3 contains the results obtained in the removal of non-plastic organic particles in the presence and absence of polystyrene microplastics.

[0157] [Table 3]

[0158] The oxidation of non-plastic organic solid particles present in real aqueous matrices of different nature by microwave-assisted Fenton process with the addition of iron and hydrogen peroxide in 5 cycles lasting 2 minutes in duration was very efficient in the presence of magnetite, achieving a removal yield of more than 80% of said particles. It is also important to emphasize that polystyrene microplastics are not affected by the oxidation treatment, and their mass is practically intact at the end of the reaction. Moreover, the nature and size of the microplastics also did not persist significantly changed after the treatment. These results clearly demonstrate the suitability of the developed oxidation process to isolate microplastics in aqueous matrices containing non-plastic organic solid particles in suspension, even when they form part of the aggregates together with magnetite.

[0159] Example 4. Quantification of microplastics present in a synthetic aqueous matrix containing organic (non-plastic) and inorganic particles using Quantification Method 1 Quantification of microplastics present in a synthetic aqueous matrix using quantification method 1 was carried out using a synthetic aqueous matrix supplemented with non-plastic organic and inorganic solid particles. The separation process was carried out using a magnetic iron mineral, namely crushed magnetite (with an average particle diameter of 0.2 μm under dry conditions and the particle size distribution shown in Figure 1). The crystalline character of the magnetite used was confirmed by X-ray diffraction analysis, which also showed that the only phase present in the solid was magnetite (Fe3O4). The percentage of iron in the magnetic minerals used was in the range of 68-78% by weight. In turn, the magnetic saturation values ​​of the materials were in the range of 70-90 emu / g, which is 70·10 in SI units. 3 ~90·10 3 Corresponds to A / m.

[0160] The experiments were carried out in glass vials into which the aqueous matrix, microplastics, non-plastic organic solid particles, inorganic solid particles and magnetite particles were introduced. The solid particles (microplastics, non-plastic organic solid particles, inorganic solid particles and magnetite particles) remained in suspension in the aqueous matrix. The conductivity and pH values ​​were measured using a conductivity meter and a pH meter, respectively. All tests were carried out using an aqueous matrix with a salt (sodium chloride) concentration of 0.1 g / L and a pH value of 7. All experiments were carried out in triplicate.

[0161] The volume of the aqueous matrix used was 50 mL, and the amount of polystyrene microplastics added was 20 mg. 50 mg of non-plastic organic solid particles (pine needles) and 20 mg of inorganic solid particles (sand), both selected in the same size range as the size range of the microplastics (all solids were sieved using a sieve with the mesh opening diameter in the size range of 100-250 μm), as well as 50 mg of magnetic iron mineral particles, were added to the suspension. The suspension was then mechanically stirred for 30 seconds using a paddle stirrer. Subsequently, a magnetic field generated by a magnet was applied to separate the magnetic solids (free magnetic iron minerals and aggregates formed between magnetic iron minerals and microplastics or non-plastic organic solid particles or inorganic particles) from the aqueous matrix. The magnetically separated solids from the aqueous matrix were filtered and dried at 105 °C for at least 2 hours. Once dried and cooled, the filter containing the solids was weighed on a precision scale and the mass of the solids was determined by weight difference against the same filter, obtaining weight A.

[0162] The magnetically separated fraction (A) was then subjected to a microwave-assisted Fenton oxidation process with the aim of selectively removing organic solids and thus making it possible to quantify the microplastic concentration.

[0163] Oxidation experiments of the non-plastic organic solid particles present in the separated magnetic fraction were carried out by resuspending said fraction in a volume of 50 mL of aqueous matrix. The oxidation reaction was carried out in a glass Erlenmeyer flask into which the aqueous matrix and the previously separated magnetic fraction (formed by aggregates and free magnetite) were introduced.

[0164] The solids forming the magnetic fraction separated in the previous step remained in suspension in the aqueous matrix. The pH of the aqueous matrix was adjusted to 3 using nitric acid. The pH value was measured using a pH meter. Iron in solution (1 mL of concentrated solution prepared using iron nitrate nonahydrate (Fe(NO3)3*9H2O) (salt concentration in the concentrated solution: 3618 mg / L) to reach a final concentration in the reaction medium of 10 mg / L) was added to the suspension as a catalyst, as was hydrogen peroxide (1 mL of concentrated solution to reach a final concentration in the medium of 5 g / L). Immediately after the reagents were added, the Erlenmeyer flask was introduced into a microwave (Teka, MW 225G model, frequency 2450 MHz) with a power of 700 W, corresponding to 55% of the maximum microwave power. Every 2 minutes, the flask was removed from the microwave and the reagents (1 mL of concentrated solution of iron and 1 mL of hydrogen peroxide solution) were added again, and this process was repeated for a total of up to 5 consecutive cycles.

[0165] Once the oxidation experiment was completed, the magnetic solid was separated from the aqueous matrix by applying a magnetic field generated by a magnet. The magnetically separated solid from the aqueous matrix was filtered and dried at 105°C for at least 2 hours. Once dried and cooled, the filter containing the solid was weighed on a precision scale and the mass of the solid was determined by weight difference against the same filter to obtain the gravimetric AF. The same filter was then subjected to combustion at 550°C for at least 1 hour until a constant mass value was reached. Once cooled, the filter containing the solid was weighed on a precision scale and the mass of the solid was determined by weight difference against the same filter to obtain the gravimetric AFM.

[0166] Mass, weight MO of non-plastic organic solid particles actually subjected to microwave-assisted Fenton oxidation process np,a was determined by Equation 2:

[0167]

number

[0168] In the formula, a is 0.8. The weight of microplastics contained in the sample (MP a ) was finally determined by Equation 1:

[0169]

number

[0170]

number

[0171]

number

[0172] Table 4 contains the average values ​​of the weights obtained and the microplastics quantified in the samples.

[0173] [Table 4]

[0174] Example 5. Quantification of microplastics present in a synthetic aqueous matrix containing organic (non-plastic) and inorganic particles using quantification method 2 Quantification of microplastics present in a synthetic aqueous matrix using quantification method 2 was carried out using a synthetic aqueous matrix supplemented with non-plastic organic and inorganic solid particles. The separation process was carried out using a magnetic iron mineral, namely ground magnetite (with an average particle diameter of 0.2 μm under dry conditions and the particle size distribution shown in Figure 1). The crystalline character of the magnetite used was confirmed by X-ray diffraction analysis, which also showed that the only phase present in the solid was magnetite (Fe3O4). The percentage of magnetic iron mineral used was in the range of 68-78% by weight. The magnetic saturation value of the material was then in the range of 70-90 emu / g, which is 70·10 in SI units. 3 ~90·10 3 Corresponds to A / m.

[0175] The experiments were carried out in glass vials into which the aqueous matrix, microplastics, non-plastic organic solid particles, inorganic solid particles and magnetite particles were introduced. The solid particles (microplastics, non-plastic organic solid particles, inorganic solid particles and magnetite particles) remained in suspension in the aqueous matrix. The conductivity and pH values ​​were measured using a conductivity meter and a pH meter, respectively. All tests were carried out using an aqueous matrix with a salt (sodium chloride) concentration of 0.1 g / L and a pH value of 7. All experiments were carried out in triplicate.

[0176] The volume of the aqueous matrix used was 50 mL and the amount of polystyrene microplastics added was 20 mg. 50 mg of non-plastic organic solid particles (pine needles) and 20 mg of inorganic solid particles (sand), both selected in the same size range as the size range of microplastics (all solids were sieved using a sieve with the mesh opening diameter in the size range of 100-250 μm), as well as 50 mg of magnetic iron mineral particles, were added to the suspension. The suspension was then mechanically stirred for 30 seconds using a paddle stirrer.

[0177] A control sample was also prepared using a 50 mL volume of aqueous matrix into which exactly the same amounts of polystyrene microplastics, non-plastic organic solid particles (pine needles), and (inorganic) solid particles were added under the same conditions as above, but without the addition of magnetic iron minerals. The suspension was also mechanically stirred for 30 seconds using a paddle stirrer. The concentration of total solids in the suspension (ST M ), as well as the concentration of fixed solids in suspension in this control sample (SI M The concentration of volatile solids (SO M ) is a total solid (ST M ) and solid solids (SI M ) can be calculated by the difference between

[0178] Next, a 50 mL volume of fresh aqueous matrix was prepared with the same amounts of polystyrene microplastics, non-plastic organic solid particles, inorganic solid particles, and magnetic iron mineral (M). The matrix was stirred for 30 seconds using a paddle stirrer.

[0179] Subsequently, a magnetic field generated by a magnet was applied to separate the magnetic solids (free magnetic iron minerals and aggregates formed between magnetic iron minerals and microplastics or non-plastic organic solid particles or inorganic particles) from the aqueous matrix (STA) and the supernatant was also collected.

[0180] The supernatant was collected on a filter and dried at 105° C. for 2 hours. Once dried and cooled, the filter containing the supernatant solids was weighed on a precision scale and the mass of the supernatant solids was determined by weight difference against the same filter, weight ST SN obtained.

[0181] The same filter was then subjected to combustion at 550° C. for at least 1 hour until a constant mass value was reached. Upon cooling, the filter containing the solids was weighed on a precision scale and the total solids in the supernatant (ST SN ) and inorganic solids (SI SN The mass of the volatile solids in the supernatant (SO ) was determined by weight difference against the same filter before it was subjected to combustion. SN) is a total solid (ST SN ) and inorganic solids (SI SN ) can be calculated by the difference between

[0182] The magnetically separated fraction (STA) was then subjected to a microwave-assisted Fenton oxidation process with the aim of selectively removing organic solids and thus making it possible to quantify the microplastic concentration.

[0183] Oxidation experiments of non-plastic organic solid particles present in the separated magnetic fraction were carried out by resuspending said fraction in a volume of 50 mL of aqueous matrix. The oxidation reaction was carried out in a glass Erlenmeyer flask into which the aqueous matrix and the previously separated magnetic fraction (formed by aggregates and free magnetite) were introduced using the reaction conditions described in Example 4.

[0184] After the Fenton process, the effluent was collected on a filter and dried at 105° C. for 2 hours. Once dried and cooled, the filter containing the total solids of the non-oxidized aggregates was weighed on a precision scale and the mass of the total solids of the non-oxidized aggregates was determined by weight difference against the same filter, weight STNOX. A obtained.

[0185] The same filter was then subjected to combustion at 550° C. for at least 1 hour until a constant mass value was reached. Once cooled, the filter containing the solids was weighed on a precision scale and the mass of the aggregated inorganic solids was determined by the weight difference against the same filter before being subjected to combustion, the weight SI A obtained.

[0186] Next, the total organic solids (SO ) of the aggregates before oxidation in Fenton were A ) was calculated as follows:

[0187]

number

[0188] The weight loss of aggregates in terms of organic matter (PPSO) was then calculated:

number

[0189] Next, the non-plastic organic matter (RMPSO) present in the sample was obtained: RMPSO=(1-(PPSO / a)) / (PPSO / a) Equation 5 In the formula, a is 0.8. The percentage of microplastics contained in the aggregates was then obtained: %MP=(1-(1 / (RMPSO+1)))* 100 Formula 4 The weight of microplastics contained in the sample (MP M ) was finally determined by Equation 3:

[0190]

number

[0191] An example of the calculations performed for one of the three iterations is shown below. The amount of magnetic mineral introduced was 50.1 mg and the volume of the aqueous matrix used was 50 mL. Obtained weight SI SN , S.T. SN , STNOX A , and S.I. A The concentrations of total solids in the suspension (ST M ), as well as the concentration of fixed solids in the suspension (SI M ) were determined in the control samples to be 90.8 mg and 20.3 mg, respectively. These parameters were calculated using the parameters SONO A , S.O. A , S.T. A , SOOX A , PPSO A , RMPSO, and %MP.

[0192]

number

[0193]

number

Claims

1. A process for determining parameters for the quantification of microplastics in an aqueous matrix containing microplastics and non-plastic organic particles, and optionally inorganic particles, comprising: a1) providing a first sample of said aqueous matrix comprising microplastics, non-plastic organic particles, and optionally inorganic particles; b1) adding magnetic iron particles to the aqueous matrix provided in step a1) to form microplastic / magnetic iron particle agglomerates and to form non-plastic organic particle / magnetic iron particle agglomerates; c1) separating the formed agglomerates and the free magnetic material particles from the mixture of step b1) by applying a magnetic field; d1) subjecting the agglomerates and the free magnetic iron material particles separated in step c1) to a drying step; e1) determining the weight of the dry solids of step d1) to obtain weight A; f1) preparing an aqueous suspension of said agglomerates obtained in step d1) and said free magnetic iron material particles; g1) subjecting the aqueous suspension prepared in step f1) to a microwave assisted Fenton process; h1) separating, preferably by filtration, the agglomerates and the free magnetic material particles present in the aqueous suspension obtained from step g1); i1) subjecting the agglomerates and the free magnetic iron material particles separated in step h1) to a drying step; j1) determining the weight of the dry solid in step i1) to obtain weight AF; k1) subjecting the agglomerates and the free magnetic material particles separated in step i1) to a combustion step; and l1) determining the weight of the solid obtained after step k1) and obtaining a gravimetric AFM; A process including.

2. A process for determining parameters for the quantification of microplastics in an aqueous matrix containing microplastics and non-plastic organic particles, and optionally inorganic particles, comprising: a2) providing a first sample of said aqueous matrix comprising microplastics, non-plastic organic particles, and optionally inorganic particles; b2) separating solids from said sample of step a2), preferably by filtration; c2) subjecting the solid separated in step b2) to a drying step; d2) Determine the weight of the dry solid of step c2) and measure the weight ST M To obtain e2) subjecting the dried solid of step c2) to a combustion step; and f2) determining the weight of the solid obtained after step e2) and calculating the weight SI M To obtain g2) providing a second sample of said aqueous matrix containing microplastics, non-plastic organic particles, and optionally inorganic particles; h2) adding magnetic iron particles to the aqueous matrix provided in step g2) to form microplastic / magnetic iron particle agglomerates and to form non-plastic organic particle / magnetic iron particle agglomerates; i2) separating the formed agglomerates and the free magnetic material particles from the mixture of step h2) by applying a magnetic field; j2) preparing an aqueous suspension of said agglomerates separated in step i2) and said free magnetic iron material particles; k2) subjecting the aqueous suspension prepared in step j2) to a microwave assisted Fenton process; l2) separating the agglomerates and the free magnetic material particles present in the aqueous suspension obtained from step k2), preferably by filtration; m2) subjecting the agglomerates and the free magnetic iron material particles separated in step l2) to a drying step; n2) Determine the weight of the dry solid in step m2) and calculate the weight STNOX A To obtain o2) subjecting the agglomerates and the free magnetic material particles separated in step m2) to a combustion step; p2) Determine the weight of the solid obtained after step o2) and calculate the weight SI A To obtain q2) filtering the remaining aqueous fraction obtained after said separation of step i2); r2) subjecting the solid separated in step q2) to a drying step; s2) Determine the weight of the dry solid of step r2) and measure the weight ST SN To obtain t2) subjecting the dried solid of step r2) to a combustion step; u2) determine the weight of the solid obtained after step t2) and calculate the weight SI SN To obtain A process including.

3. 3. The process according to claim 1 or 2, wherein the weight of the magnetic iron material particles added to the aqueous matrix in step b1) or h2) is 0.1 to 20 times the weight of the particles in suspension in the aqueous matrix provided in step a1) or g2), respectively.

4. 4. The process according to any of claims 1 to 3, wherein the magnetic iron material comprises an iron species selected from the group consisting of Fe(II), Fe(III), metallic Fe, and mixtures thereof, preferably the magnetic iron material is magnetite.

5. A process according to any of the preceding claims, wherein the average diameter of the magnetic iron mineral particles is comprised between 0.05 and 10 μm, preferably between 0.1 and 0.3 μm.

6. 6. The process according to any of claims 1 to 5, wherein the microplastics are selected from the group consisting of polystyrene (PS), polyethylene terephthalate (PET), polyethylene (PE) including high density polyethylene (HDPE) and low density polyethylene (LDPE), polyvinyl chloride (PVC), polypropylene (PP), polycarbonate (PC) and polyurethane (PU), and mixtures thereof.

7. The process according to any of claims 1 to 6, wherein the mixture obtained in step b1) or / and h2) is subjected to stirring before carrying out step c1) or / and i2), respectively, preferably said stirring is mechanical or magnetic stirring, more preferably mechanical stirring.

8. The process according to any of claims 1 to 7, wherein the separation of steps c1) and / or i2) is carried out using a magnet or an electromagnet.

9. 9. The process according to any of claims 1 to 8, wherein in step g1) or k2) hydrogen peroxide and an iron salt are added, preferably hydrogen peroxide and an iron salt selected from the group consisting of iron nitrate, iron chloride, iron sulfate and mixtures thereof, more preferably hydrogen peroxide and iron nitrate.

10. 10. The process according to claim 9, wherein the iron salt concentration in the aqueous suspension of step g1) or k2) is in the range of 1 mg / L to 1000 mg / L and / or the hydrogen peroxide concentration in the aqueous suspension of step g1) or k2), respectively, is in the range of 10 mg / L to 100 g / L.

11. The process according to any of the preceding claims, wherein step g1) or k2) is carried out at a microwave power in the range of 50 to 1500 W and / or for a time in the range of 1 s to 2 h.

12. The process according to any of claims 1 to 11, wherein the pH of the aqueous suspension of steps g1) and / or k2) is adjusted to be in the range of 2 to 4.

13. 13. The process according to any of the preceding claims, wherein the combustion of steps k1), e2), o2) and / or t2) is carried out by subjecting the solid to a temperature between 500°C and 600°C for a period of 1 to 4 hours.

14. A process for the quantification of microplastics in an aqueous matrix containing microplastics and non-plastic organic particles, and optionally inorganic particles, comprising: I-1) carrying out steps a1) to l1) of the process for determining parameters according to claims 1 and 3 to 13 for determining weights A, AF and AFM; II-1) Weight of microplastics (MP A ) to calculate: [0010] During the ceremony, A is the weight of solids determined in step e1) of the process according to claims 1 and 3 to 13, AFM is the weight of solids determined in step l1) of the process according to claims 1 and 3 to 13, M.O. NP,A is calculated using Equation 2, [0025] wherein A is the weight of solids determined in step e1) of the process according to claims 1 and 3 to 13, AF is the weight of solids determined in step j1) of the process according to claims 1 and 3 to 13 and a is a number between 0.7 and 1, preferably between 0.8 and 0.9, most preferably 0.

8.

15. A process for the quantification of microplastics in an aqueous matrix containing microplastics and non-plastic organic particles, and optionally inorganic particles, comprising: I-2) Weight ST M、 S.I. M , STNOX A , S.I. A , S.T. SN , and S.I. SN carrying out steps a2) to u2) of the process for determining a parameter according to claims 2 to 13 for determining II-2) The weight of microplastics (MP M ) to calculate: [0030] During the ceremony, %MP is calculated using Equation 4: [0045] where RMPSO is calculated using Equation 5: [0050] where a is a number between 0.7 and 1, preferably between 0.8 and 0.9, and most preferably 0.8, and the PPSO is calculated using Equation 6: [006] During the ceremony, STNOX A is the weight of solids determined in step n2) of the process according to claims 2 to 13, SI A is the weight of solids determined in step p2) of the process according to claims 2 to 13, and SO A is calculated using Equation 7, [0070] In the formula, SI A is the weight of solids determined in step p2) of the process according to claims 2 to 13, SI SN is the weight of solids determined in step u2) of the process according to claims 2 to 13, and ST SN is the weight of solids determined in step s2) of the process of claims 2 to 13, M is the weight of magnetic material particles added in step h2) of the process of claims 2 to 13, ST M is the weight of solids determined in step d2) of the process according to claims 2 to 13, SI M is the weight of solids determined in step f2) of the process according to claims 2 to 13.